Characteristics and risk factors of secondary bacterial infections in COVID-19 patients - Guangjie Wu; Jianhua Lu; Dong Liu; Yan He (Cambridge University Press, 2023)
Abstract Objective: To describe the characteristics and find out risk factors of COVID-19 patients infected with different categories of bacteria. Design: Case-control. Methods: We conducted a retrospective study including 129 COVID-19 patients admitted to a tertiary hospital between October 13, 2022 and December 31, 2022. Patients' data were collected from the hospital information system. Patients were classified as having or not having confirmed secondary bacterial infections, or gram-positive and gram-negative bacterial infections for analysis. Categories and sources of isolated bacteria, characteristics of the patients, and the risk factors for developing secondary bacterial infections were analyzed. Results: Gram-negative bacteria accounted for the majority of secondary bacterial infections of the included patients. Critical type of COVID-19 (OR = 12.98, 95%CI 3.43∼49.18, p < 0.001), invasive therapy (OR = 9.96, 95%CI 3.01∼32.95, p < 0.001), and previous antibiotics use (OR = 17.23, 95%CI 1.38∼215.69, p = 0.027) were independent risk factors of secondary bacterial infections in COVID-19 patients. Ceftriaxone/cefotaxime use (OR = 15.45, 95%CI 2.72∼87.79, p = 0.002) was associated with gram-positive bacterial infections while age over 70 (OR = 3.30, 95%CI 1.06∼10.26, p = 0.039), invasive therapy (OR = 4.68, 95%CI 1.22∼17.93, p = 0.024), and carbapenems use (OR = 8.48, 95%CI 2.17∼33.15, p = 0.002) were associated with gram-negative bacterial infections. Conclusions: Critical patients with invasive therapy and previous antibiotics use should be cautious with secondary bacterial infections. Third-generation cephalosporins and carbapenems should be used carefully because both are risk factors for gram-positive or gram-negative bacterial infections.